Effects of Oraganizing Learning with Differentiated Instruction by Using a Graphic Organizer for Development of Creative Writing Skills of Fourth Grade Students - Paensuk, Luxamee; Lanchwathanakorn, Chattrawan (An Online Journal of Education, 2020)
The purposes of this research were 1) to compare creative writing skills of fourth grade students before and after organizing learning with differentiated instruction by using graphic organizers, and 2) to study opinions of fourth grade students who participated in differentiated instruction by using graphic organizers. The research sample included 93 fourth grade students of Saimai (Thatsanarom-anusorn) school during first semester of the 2019 academic year. The research instruments consisted of lesson plans for differentiated instruction by using graphic organizers and two items of creative writing skills tests. The data were analyzed by using descriptive statistics, t-test dependent and content analysis. The results of this research showed that 1) creative writing skills of fourth grade students after organizing learning with differentiated instruction by using graphic organizers were higher than before at a statistically significant level of .05, and 2) fourth grade students who participated in differentiated instruction by using graphic organizers expressed satisfaction and the opinion that organizing learning with differentiated instruction by using graphic organizers assisted the development of their creative writing skills.